PERAMALAN NILAI TUKAR PETANI SUBSEKTOR TANAMAN PANGAN PROVINSI BALI MENGGUNAKAN METODE FUZZY TIME SERIES CHEN - AENI, ULYATIL; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika; Vol 12 No 2 (2023)DO - 10.24843/MTK.2023.v12.i02.p407, 2023)
Forecasting is a way to predict future events. One of the methods for forecasting is to use fuzzy time series Chen method. Fuzzy time series Chen is a development of fuzzy time series Song and Chissom method with more simplified arithmetic operations. In this study, the forecasting for the NTP especially in food crops sub-sector of Bali was done by using first-order and high-order fuzzy time series methods to predict next period. The results show that the most appropriate forecasting method is the second-order fuzzy time series Chen with the result for June 2022 are 90.95, July 2022 are 91.95, and August 2022 are 92.45 with MSE value of 0.4563 and MAPE value of 0.2824%.